Math, asked by masterchefstirl6665, 11 months ago

Solve the following quadratic equations by factorisation method 3x^2-2√6x+2

Answers

Answered by amansharma264
0

Answer:

 {3x}^{2} - 2 \sqrt{6x } + 2 \\ d = {b}^{2} - 4ac \\  (- 2 \sqrt{6}) {}^{2} - 4(3)(2) \\ 24 - 24 \\  = 0 \\ d = 0 \\ x = \frac{ - b +  \sqrt{d} }{2a} \\ \frac{ - ( - 2 \sqrt{6) } +  \sqrt{0}  }{6} \\  \frac{2 \sqrt{6} }{6} \\  \frac{ \sqrt{6} }{3} \\  =  \frac{ - b -  \sqrt{d} }{2a} \\  \frac{ - ( - 2 \sqrt{6)} -  \sqrt{0}  }{6} \\  \frac{2 \sqrt{6 \ } }{6} \\  \frac{ \sqrt{6} }{3} = answer

please mark as brilliant answer

Similar questions